Loopholes in Public Policy Making: A Case Study of Pakistan - Iram Khalid; Muhammad Mushtaq; Arooj Naveed (Journal of Political Studies, 2016)
In developing countries, making of a public policy features resolutions of problems entrenched in policy community and policy network. Its formulation does not only require decisions taken only from the highest authority but also includes enticement and involvement of many new actors bringing in additional actors and inducements important for a policy design. The paper attempts to study making of public policy in developing countries. Following the dominant model bureaucratic politics, various approaches, their policy designs, tools of policy, integration and involvement of actors, their discourse related to their policy communities and their networks of policy are studied to understand and learn lesson and important elements necessary for formulation of a policy. Further, reasons for loopholes and failures in public policy formulation have been elaborated by studying the case of Pakistan. In conclusion, the way forward for positive policy outcomes has been detailed by highlighting the concept of citizen participation and focusing on four focal areas of process, quality, structure and politics required for practicing and implementing policies in theory and practice.